2022
DOI: 10.1192/bjo.2022.12
|View full text |Cite
|
Sign up to set email alerts
|

Staff support in a National Health Service mental health trust in response to the COVID-19 pandemic: qualitative study

Abstract: Background The COVID-19 pandemic has highlighted the impact work can have on healthcare workers and the importance of staff support services. Rapid guidance was published to encourage preventive and responsive support for healthcare workers. Aims To understand mental healthcare staff's help-seeking behaviours and access to support at work in response to the COVID-19 pandemic, to inform iterative improvements to provision of staff support. Method We conducted a formative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…Our study also found alarmingly high exposure to negative workplace experiences related to harassment and discrimination among ethnically minoritised NHS staff during the pandemic. These findings are consistent with the most recent NHS staff survey 1 and UK-REACH 34 in addition to being supported by multiple qualitative studies that have explored similar workplace experiences among ethnically and racially minoritised groups [35][36][37] . The short-term and long-term impacts of such experiences are likely to take a toll on the mental and physical health of employees [38][39][40] , as well as their dependents and social networks, with implications for career progression, intention to remain at the NHS, and salary 2 .…”
Section: Discussionsupporting
confidence: 88%
“…Our study also found alarmingly high exposure to negative workplace experiences related to harassment and discrimination among ethnically minoritised NHS staff during the pandemic. These findings are consistent with the most recent NHS staff survey 1 and UK-REACH 34 in addition to being supported by multiple qualitative studies that have explored similar workplace experiences among ethnically and racially minoritised groups [35][36][37] . The short-term and long-term impacts of such experiences are likely to take a toll on the mental and physical health of employees [38][39][40] , as well as their dependents and social networks, with implications for career progression, intention to remain at the NHS, and salary 2 .…”
Section: Discussionsupporting
confidence: 88%
“…These findings are consistent with the most recent NHS staff survey 1 and UK-REACH 31 in addition to being supported by multiple qualitative studies that have explored similar workplace experiences among ethnically and racially minoritised groups. [32][33][34] The short-term and long-term impacts of such experiences are likely to take toll on the mental and physical health of employees, 35 as well as their dependents and social networks, with implications for career progression, intention to remain at the NHS and salary. 2…”
Section: Discussionmentioning
confidence: 99%
“…When a system is in chronic stress, it creates a barrier for clinicians to access support, even when that support is available (Smith et al, 2022). In formulating a standardized emotional debriefing model, there are several factors to consider.…”
mentioning
confidence: 99%